Digital education governance: An introduction. (January 2016) - Williamson, Ben
Educational governance today increasingly needs to be understood as digital educational governance. The monitoring and management of educational systems, institutions and individuals is taking place through digital systems that are normally considered part of the backdrop to conventional policy instruments and techniques of government; technical systems that are brought into being and made operational by certain kinds of actors and organizations, and that are imbued with aims to shape the actions of human actors distributed across education systems and institutions. The aim of the original articles collected in this special issue of the European Educational Research Journal is to bring into the foreground the digital technologies, software packages, database platforms and related forms of technical expertise involved in the rise of digital educational governance. The authors seek to understand how such digital technologies and techniques may be contributing to, or transforming, trends such as governing through data, the globalizing and Europeanizing of educational policy, accountability and performativity, global comparison and benchmarking, and to emerging local, national and supranational objectives.